Empowerment of Coral Cadets In Cibiru Hilir Village In Building A Creative Economy Through Hydroponic And Aquaponic Training - Dede Margo Irianto; Yusuf Tri Herlambang; Hana Yunansah; Yunus Abidin; Rahman Wahid; Arif Sarifudin; M Nizan Solehudin (LPPM Universitas Muhammadiyah Tasikmalaya, 2022)
the Objective of the program of community service is To Empowering Karang Taruna Desa Cibiru Hilir In Building the Creative Economy Through Training on Hydroponics And Aquaponics. Weaknesses of teachers in making learning media makes the problem to be the solution sought. Hydroponics and aquaponics is one of the alternatives to build the creative economy of the community, so that it becomes the basis and the reason of rational team of researchers in taking steps to implement community service activities through training sistemhidroponik and aquaponics. Community service is performed by the method of the development of action research. Community service activities in his youth in the Village Cibiru Hilir, Kecamatan Cileunyi, Bandung Regency in accordance with the results of the response of the questionnaire the level of satisfaction of partners in the implementation of community service, which said that the partners respond to a positive response (90%) with the activity of this devotion.